The rise and decline of Thai absolutism - Mead, Kullada Kesboonchoo, 1943- (RoutledgeCurzon, 2004)
This book examines the development of Thailand from the integration of Siam into the European world economy at the beginning of the 19th century, up to the emergence of Thailand as a modern nation state in the 20th century.
Keywords: Despotism -- Thailand -- History.; Thailand -- Politics and government -- 1782-1945.; Despotisme -- Thaïlande -- Histoire.; Thaïlande -- Politique et gouvernement -- 1782-1945.; HISTORY.; Despotism; Politics and government; Thailand; 1782-1945; Electronic books.; History